2002
DOI: 10.1346/000986002320514190
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dissolution Kinetics of Al-Substituted Goethites

Abstract: Several Al-substituted goethites were synthesized by hydrolysis of Fe3+ salt solutions. The kinetics of the reductive dissolution of these goethites in dithionite-ethylenediaminetetra acetic acid (D-EDTA) was studied at pH 5.5, at 303, 323 and 333 K. The initial dissolution rate (R) per unit of surface area decreases with Al substitution. In the sample with greater Al content (G″7), the kinetic profiles of the dissolved Fe fraction vs. time gave a small positive intercept. The kinetic profile of R as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Previous research by Gonzalez et al (2002) also found that the surface area of goethite did not change considerably with Al substitution. In contrast, however, Al substitution within lepidocrocite resulted in a substantial increase in surface area -increasing from 144 to 255 m 2 g À1 with the incorporation of 13 mol% Al ( Table 2).…”
Section: Impact Of Al Substitution On Mineral Physiochemical Propertiesmentioning
confidence: 66%
“…Previous research by Gonzalez et al (2002) also found that the surface area of goethite did not change considerably with Al substitution. In contrast, however, Al substitution within lepidocrocite resulted in a substantial increase in surface area -increasing from 144 to 255 m 2 g À1 with the incorporation of 13 mol% Al ( Table 2).…”
Section: Impact Of Al Substitution On Mineral Physiochemical Propertiesmentioning
confidence: 66%
“…Changes in the physicochemical and electrical properties of the phases, however, are a function of the cation type and Fe(III) (hydr)oxide structure. For instance, while Al substitution in goethite results in lower solubility (Schwertmann, 1984;Torrent et al, 1987;Alvarez et al, 2007;Ekstrom et al, 2010) and a slight decrease in surface area (Gonzalez et al, 2002;Ekstrom et al, 2010), the opposite occurs for Al-substituted lepidocrocite (Schulze and Schwertmann, 1984;Schwertmann and Wolska, 1990;Ekstrom et al, 2010). Although natural Fe(III) (hydr)oxides are seldom pure, little is known about the impact of substituted ions on the conversion of Fe(III) phases in the presence of abiotic (Jones et al, 2009) and/or biotic (Bousserrhine et al, 1999;Fredrickson et al, 2001;Kukkadapu et al, 2001Kukkadapu et al, , 2004Dominik et al, 2002;Ekstrom et al, 2010) reductants.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-substitution in ferrihydrite alters its propensity to transform into crystalline phases and the rate and extent of reductive and proton-enhanced dissolution (Schwertmann, 1984;Bousserrhine et al, 1998;Schwertmann et al, 2000;Gonzalez et al, 2002;Jentzsch and Penn, 2006). For example, after 16 years of aging at 25°C across a pH range of 4-7 in aerated suspension, only a minor fraction of Al-substituted ferrihydrite was transformed (predominantly to hematite), while the majority of pure ferrihydrite was transformed to goethite (Schwertmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, after 16 years of aging at 25°C across a pH range of 4-7 in aerated suspension, only a minor fraction of Al-substituted ferrihydrite was transformed (predominantly to hematite), while the majority of pure ferrihydrite was transformed to goethite (Schwertmann et al, 2000). The rate of synthetic goethite dissolution via proton-enhanced dissolution in 6 M HCl decreased markedly with increasing Al substitution (Schwertmann, 1984), as did abiotic reductive dissolution with dithionite-EDTA at pH 5.5 (Gonzalez et al, 2002) and reductive dissolution by acid producing fermentative bacteria (Bousserrhine et al, 1998). On the other hand, the rate of ferrihydrite reduction by hydroquinone at pH 3.75 increased with increasing Al substitution (at substitutions ranging from 0 to 2.1 mole-% Al) (Jentzsch and Penn, 2006).…”
Section: Introductionmentioning
confidence: 99%